Resolving Conflicts Over Ethical Issues: Face-to-face Versus Internet Negotiations - van Es, Robert (Journal of business ethics, 2004)
Is the Internet an appropriate medium to use when attempting to resolve conflicts over ethical issues in business? The research reported on in this paper focuses on internet versus face-to-face negotiations as a component of applied discourse ethics. Although internet negotiation has serious restrictions, it also has specific qualities. It enhances reflection and plays down emotion. Important qualities when handling complex and delicate ethical issues.